2011
DOI: 10.1111/j.1365-2672.2011.05031.x
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli in children with acute diarrhoea and controls in Teresina/PI, Brazil: distribution of enterotoxin and colonization factor genes

Abstract: Aims:  To investigate the distribution of the genes that encode enterotoxins and the colonization factors (CF) types as well as the antibiotic susceptibility profile of enterotoxigenic Escherichia coli (ETEC) isolated from children from the Brazilian Northeast. Methods and Results:  We conducted a 3·5‐year prospective study that involved 250 children with and 150 without diarrhoea, aged 1–60 months, from low‐income families in Teresina/Brazilian Northeast. All samples were assayed for E. coli, enterotoxin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
(142 reference statements)
2
7
2
Order By: Relevance
“…The proportion of the ETEC strains isolated from children with diarrhea that were CF positive was significantly higher than the proportion of ETEC isolates from control children as previously described for ETEC strains in Bangladesh (25), suggesting that the presence of CFs is related to virulence. In our study, CFA/I SThonly or LT/STh strains were the most common combinations of ETEC strains isolated from diarrhea cases, similar to recent reports from Brazil and Bangladesh (20,26). During 2007, comparably high prevalences of CS14-positive ETEC infections were reported, but the prevalence of CS14 ETEC infections was dramatically reduced during the following years, suggesting a possible outbreak of such strains in 2007.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The proportion of the ETEC strains isolated from children with diarrhea that were CF positive was significantly higher than the proportion of ETEC isolates from control children as previously described for ETEC strains in Bangladesh (25), suggesting that the presence of CFs is related to virulence. In our study, CFA/I SThonly or LT/STh strains were the most common combinations of ETEC strains isolated from diarrhea cases, similar to recent reports from Brazil and Bangladesh (20,26). During 2007, comparably high prevalences of CS14-positive ETEC infections were reported, but the prevalence of CS14 ETEC infections was dramatically reduced during the following years, suggesting a possible outbreak of such strains in 2007.…”
Section: Discussionsupporting
confidence: 88%
“…However, variations in toxin profiles were observed from year to year. Different studies in Latin America have shown differences in the predominant toxin type; for instance, LT/ST ETEC strains were found to be most prevalent in Peru (19), ST-only ETEC strains in Brazil (20) and LT ETEC strains in Argentina (23), in Nicaragua (21), and in a previous report from Bolivia (16). A similar trend has been observed in Bangladesh, where different toxin profiles have predominated over the years (24)(25)(26).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…ETEC in children with acute diarrhoea and controls in Teresina/PI, Brazil overall, CF genes were identified in 53·3% (32/60) of the ETEC strains isolated from 19 (67·6%) children, 15 (78·9%) with diarrhoea and four (21·1%) controls (Nunes et al . ). In Peruvian children effected with ETEC, CFs were identified in 64% of diarrhoeal samples and 37% of control samples (Rivera et al .…”
Section: Discussionmentioning
confidence: 97%
“…The CS14 and CFA/IV were the most common CFs in Teresina, Brazil (Nunes et al . ). In Bangladesh, the predominant CFs were CS6, CS5, CFA/I, CS7, CS17, CS1, CS3 and CS14 (Begum et al .…”
Section: Introductionmentioning
confidence: 97%